Metabolomic profiling of Dezhou donkey seminal plasma related to freezability. Issue 10 (25th June 2022) - Wang, Zhaofei; Yu, Jie; Zhong, Shuai; Fan, Zhaobin; Wang, Fuwen; Ji, Chuanliang; Wang, Yantao; Lei, Chuzhao; Dang, Ruihua; Zhao, Fuwei
Abstract: Donkeys are indispensable livestock in China because they have transport function and medicinal value. With the popularization of artificial insemination on donkeys, semen cryopreservation technology has gradually become a research hotspot. Seminal plasma is a necessary medium for transporting sperm and provides energy and nutrition for sperm. Seminal plasma metabolites play an important role in the process of sperm freezing, and also have an important impact on sperm motility and fertilization rate after freezing and thawing. In this study, liquid chromatography–tandem mass spectrometry (LC–MS/MS) analysis was used to compare the metabolic characteristics of seminal plasma of high freezability (HF) and low freezability (LF) male donkeys. We identified 672 metabolites from donkey seminal plasma, of which 33 metabolites were significantly different between the two groups. Metabolites were identified and categorized according to their major chemical classes, including homogeneous non‐metal compounds, nucleosides, nucleotides, and analogues, organosulphur compounds, phenylpropanoids and polyketide, organoheterocyclic compounds, organic oxygen compounds, benzenoids, organic acids and derivatives, lipids and lipid‐like molecules, organooxygen compounds, alkaloids and derivatives, organic nitrogen compounds. The results showed that the contents of phosphatidylcholine, piceatannol and enkephalin in donkey semen of HF group were significantly higher than those of LF group ( p  < .05), while the contents of taurocholic and lysophosphatidic acid were significantly lower than those of LF group ( p  < .05). The different metabolites were mainly related to sperm biological pathway response and oxidative stress. These metabolites may be considered as candidate biomarkers for different fertility in jacks.